Differential Induction of Complement Fragment C5a and Inflammatory Cytokines during Intramammary Infections with Escherichia coli and Staphylococcus aureus - Riollet, Céline (American Society for Microbiology, 2000)
The prompt recruitment of neutrophils to the site of infection is essential for the defense of the bovine mammary gland against invading pathogens and is determinant for the outcome of the infection. Escherichia coli is known to induce clinical mastitis, characterized by an intense neutrophil recruitment leading to the eradication of the bacteria, whereas Staphylococcus aureus induces subclinical mastitis accompanied by a moderate neutrophil recruitment and the establishment of chronic mastitis. To elicit the neutrophil recruitment into the udder, inflammatory mediators must be produced after recognition of the invading pathogen. To our knowledge, those mediators have never been studied during S. aureus mastitis, although understanding of the neutrophil recruitment mechanisms could allow a better understanding of the differences in the pathogeneses elicited by E. coli and S. aureus. Therefore, we studied, at several time points, the accumulation of neutrophils and the presence of the chemoattractant complement fragment C5a and of the cytokines interleukin-1β (IL-1β), tumor necrosis factor alpha, and IL-8 in milk after inoculation of E. coli or S. aureus in lactating bovine udders. The low levels of C5a and the absence of cytokines in milk from S. aureus-infected cows, compared to the high levels found in milk from E. coli-infected animals, mirror the differences in the severities of the two inflammatory reactions. The cytokine deficit in milk after S. aureus inoculation in the lactating bovine mammary gland could contribute to the establishment of chronic mastitis. This result could help in the design of preventive or curative strategies against chronic mastitis.